STUDI PREFERENSI PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) BAGI EFISIENSI BIAYA PRODUKSI DI PT PABRIK GULA KEBON AGUNG - Monica Kurniawati (Ma Chung Press, 2016)
The purpose of this research is to assess the preference of TQM application for the production cost efficiency and also to assess the preference wanted than the application of TQM for the production cost efficiency in PT Pabrik Gula Kebon Agung. This research is using conjoint analysis method to measure the preferences of TQM application for the production cost efficiency in PT Pabrik Gula Kebon Agung. The result of the research shows that the highest preference from the respondents is in the TQM factor in form of obsession towards quality related with the production cost in the company. Respondents assumed that the quality is appropriate or that the cost is still not appropriate with the product produced and tend to show that the quality is not appropriate. The result also showed that the respondents in PT Pabrik Gula Kebon Agung prioritize the obsession over quality to make production cost efficient that pointed towards analysis of priority. Then, respondents prioritize the involvement of employees in production cost efficiency, focused on customers, and the last is a long-term commitment in the employee related to production cost efficiency.